Pengaruh Budaya Organisasi dan Gaya Kepemimpinan Terhadap Produktivitas Kerja Pegawai Di Pemerintah Daerah - Indrawati, Lili; Sembiring, Etti Ernita (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
The purpose of this research is to analyze and prove the role of organizational culture and leadership style against employee productivity in local government. The research was carried out at the West Bandung Local Government, by distributing the questionnaires to 27 work unit, each unit for 4 respondences . The distribution of queationnaires was carried out during the 2 month pandemic. The reseach sample is the financial manager and staf in the work unit and the sampling technique uses the purposive sampling method. The data analysis tool used is multiple regresion. The results shows that organizatinal culture and leadership style simultaneously have a pocitive effect on emplyoyee productivity